Alice in wonderland - Alice au pays des merveilles : a French to English bilingual book with French to English dictionary - Carroll, Lewis (MostUsedWords, 2019)
Alice falls into a rabbit hole and a strange universe where nothing is as it seems. This dual language story is made specifically for language learners and is aligned with the original English version of the story side-by-side with the official French translation by Henri Bué. It includes two dictionaries to aid with learning French: a frequency dictionary and an alphabetical dictionary